(untitled) (LACCEI, 2024)
The objective of the research was to determine the level of entrepreneurship in young people from 18 to 30 years old in times of pandemic in Northern Peru. The research was applied, with a non-experimental cross-sectional design. There was a sample of 300 young entrepreneurs between 18 and 30 years of age in northern Peru. The technique used was a survey with a questionnaire of 23 questions applied to each young entrepreneur, in this way the necessary data were collected and then processed in the Excel program to respond to the objectives set. The first result obtained was that the level of entrepreneurship in young people aged 18 to 30 years in times of pandemic, fluctuates between very high and medium, with percentages that together make 85.3%, which indicates that entrepreneurship in times of pandemic in young people has been maintained, since some have been able to seize opportunities despite the circumstances presented to them in these times of crisis. Likewise, 33% of the young people stated that the clothing sales area was the area with the highest level of entrepreneurship, out of 25 areas.